Variations in aroma and specific flavor in strawberry under different colored light‐quality selective plastic film. (18th February 2020) - Peng, Xin; Wang, Bin; Wang, Xile; Ni, Binbin; Zuo, Zhaojiang
Abstract: Strawberry aroma is beneficial to the quality of the fruits and derived foods, as well as consumer health. Light quality affects strawberry aroma emission, which can be conveniently supplied by colored light‐quality selective plastic films. To produce high‐aroma strawberry by using optical colored light‐quality selective plastic film, the aroma emission and key gene expression were investigated under transparent (T), red (R), yellow (Y), green (G), blue (B), and purple (P) films. Moreover, the content of sugar, soluble proteins, and anthocyanins as well as total titratable acidity was also investigated. Strawberry released an abundance of aroma, mainly including esters, terpenoids, alkanes, alcohols, acids, aldehydes, and ketones. T, R, and Y films increased FaAAT (alcohol acyltransferase) expression to promote ester emission. Among strawberry aroma components, trans‐nerolidol showed the maximum emission amount. R film promoted its emission by increasing FaNES1 (nerolidol synthase) expression. Meanwhile, R film was also beneficial to the accumulation of reducing sugar, sucrose, total sugar, anthocyanins, and soluble proteins, and total titratable acidity. Therefore, high‐aroma strawberry can be produced by using R light selective plastic film, with increasing fruit chemical properties. Abstract : Among different colored light‐quality selective plastic films, the red film remarkably improved the fruit aroma by promoting related gene expression, and also improved the fruit flavor by increasing the content of sugar, anthocyanins and soluble proteins, as well as total titratable acidity, indicating that this film should be the optical choice in building greenhouse for strawberry production.